Assessing resistance to late blight of potato: methods used at the Scottish Crop Research Institute - Stewart, Helen E.; Solomon-Blackburn, Ruth (Plant Breeding and Seed Science, 2004)
At SCRI, wild species and clones of Solanum tuberosum are assessed for resistance to late blight in order to study the genetics and breed for resistance. Glasshouse progeny tests for foliage and tuber blight resistance, using true seedlings, are described. These enable the rapid screening of accessions of wild species, and the selection of the most resistant progenies in a breeding programme within one year of crossing. Assessment of the foliage resistance of clones is carried out in glasshouse tests of whole plants in flower-bud, and field trials using infector plants inoculated in the glasshouse with a complex race of Phytophthora infestans. The glasshouse test provides a reliable method of identifying R-genes and the virulence characteristics of blight isolates. The field trial gives the best estimate of field resistance and is being used to develop marker-assisted selection. Both tests are used to study the inheritance of resistance, to locate quantitative trait loci (QTL) and R-genes, and to select the most resistant clones. The tuber resistance of clones is assessed by spray-inoculating whole, immature, field-grown tubers on the day of harvest. However when large numbers of clones are involved, e.g. in the location of QTL, this is impractical, so glasshouse-grown tubers are dip-inoculated.